2014
DOI: 10.1038/onc.2014.49
|View full text |Cite
|
Sign up to set email alerts
|

KAP regulates ROCK2 and Cdk2 in an RNA-activated glioblastoma invasion pathway

Abstract: Aberrant splicing of the cyclin-dependent kinase-associated phosphatase, KAP, promotes glioblastoma invasion in a Cdc2-dependent manner. However, the mechanism by which this occurs is unknown. Here we show that miR-26a, which is often amplified in glioblastoma, promotes invasion in phosphatase and tensin homolog (PTEN)-competent and PTEN-deficient glioblastoma cells by directly downregulating KAP expression. Mechanistically, we find that KAP binds and activates ROCK2. Thus, RNA-mediated downregulation of KAP l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Although migrating cells activate Rho GTPases to control myosin phosphorylation and cell motility, they also control GC activity and cGMP increase [43]. Indeed, GBM invasiveness has been shown to be strongly induced by negative regulation of ROCK2 activity [4446]. We demonstrated that ROCK inhibition increased GBM invasiveness and increased Ser695 MYPT1 levels, similarly to what has been described for rat neuronal migration [47].…”
Section: Discussionsupporting
confidence: 81%
“…Although migrating cells activate Rho GTPases to control myosin phosphorylation and cell motility, they also control GC activity and cGMP increase [43]. Indeed, GBM invasiveness has been shown to be strongly induced by negative regulation of ROCK2 activity [4446]. We demonstrated that ROCK inhibition increased GBM invasiveness and increased Ser695 MYPT1 levels, similarly to what has been described for rat neuronal migration [47].…”
Section: Discussionsupporting
confidence: 81%
“…Rock2 belongs to the serine/threonine protein kinase family. The studies reported that Rock2 is closely associated with the occurrence and development of HCC [18]. Our previous research also revealed that Rock2 overexpression inhibits the ubiquitination‐mediated degradation of MMP2, thereby promoting HCC invasion and metastasis [10].…”
Section: Discussionmentioning
confidence: 91%
“…Tumor volume was calculated according to the formula V (mm 3 ) = a × b 2 /2, where a is the longest diameter, and b is the shortest diameter of the tumor. The number of invading cells outside the tumor core was quantitatively analyzed according to previous reports 32, 33 .…”
Section: Methodsmentioning
confidence: 99%